THE INFLUENCE OF EMPLOYEE ENGAGEMENT ON TURNOVER INTENTION AMONG STAFF AT YAPIKA GENERAL HOSPITAL IN 2025 - Andi Nur Faizah Zahirah; Rusmin, Muhammad; Raodhah, Sitti; Satrianegara, M. Fais (Universitas Islam Negeri Alauddin Makassar, 2025)
Background: Employee engagement is a crucial factor influencing workforce performance and sustainability in hospitals. Low employee engagement may increase turnover intention, leading to high recruitment costs, declining service quality, and reduced patient satisfaction. Objective: This study aims to analyze the influence of employee engagement on turnover intention among staff at Yapika General Hospital in 2025. Method: A quantitative research design with a cross-sectional approach was applied, involving 131 respondents selected through proportional sampling. Data were collected using the Gallup Q12 questionnaire with a 5-point Likert scale, and analyzed using univariate and bivariate methods with simple linear regression. Result: The findings show that the majority of respondents were not engaged (91.6%), with most having a moderate level of turnover intention (67.9%). Regression analysis revealed a significant effect of employee engagement on turnover intention (t = -10.987; p = 0.000). Conclusion: Furthermore, all four engagement dimensions (basic needs, management support, teamwork, and growth) showed significant negative effects on turnover intention. In conclusion, higher employee engagement reduces staff’s intention to resign. Therefore, enhancing engagement through fulfilling basic needs, managerial support, teamwork, and career development opportunities is essential to reduce turnover intention and maintain hospital service quality.